A case of severe cutaneous and mucosal erosions. (1st August 2020) - Korbl, J. D.; Brusch, A.; Lucas, M.; von Nida, J.; Wood, B. A.; Leecy, T. N.; Harvey, N. T.
Abstract: Click here for the corresponding questions to this CME article.